Learn how to grow onions, garlic and leeks - Ngeze, P.B. (Acacia Stantex Publishers / CTA / Friends-of-the-Book Foundation, 2001)
Onions, garlic and leeks tend to be overlooked in food production literature. Translated from the Kiswahili edition, this booklet describes the conditions conducive to producing these vegetables, the diseases that affect them, and harvesting and storage methods.